Church Architecture in Southwestern Bulgaria in the Late 9th – Early 11th Century (Based on Archaeological Data) - Georgieva, Miroslava (Studia Ceranea, 2023)
This publication is devoted to the church architecture in Southwestern Bulgaria (now Blagoevgrad region) during the First Bulgarian Tsardom, in the period from the end of the 9th to the beginning of the 11th century. From the second half of the 9th century (specifically from 864) the territories of the region under consideration officially entered the borders of the medieval Bulgarian state, which coincided with the conversion to Christianity in Bulgaria (865). The studied region covers the valleys of the rivers of Struma (Middle Struma) and Mesta (Upper and Middle Mesta), which were part of the southwestern borders of the Bulgarian state in the Middle Ages. At present, three churches can be attributed to this period, all excavated through regular archaeological excavations. These are the Basilica of St. Nicholas in the town of Melnik, the single-nave church in the area of Shipotsko at the town of Bansko and the three-conchal church at the village of Kulata, Petrich municipality. In terms of their functional characteristics, these churches include an episcopal (or parish) church (“St. Nicholas” in Melnik), a cemetery church (the church in the area of Shipotsko near the town of Bansko) and a monastery church (the church at the village of Kulata). Characteristic for the first two is their construction on older cult sites – on an ancient sanctuary and an early Christian church (the church “St. Nicholas” in Melnik) and on an early Christian temple (the church in the area of Shipotsko, at the town of Bansko). The small number of excavated church buildings from the First Bulgarian Tsardom is also typical for the rest of the Bulgarian lands. Although the examples from the region are few, they show that almost all major architectural types are found here.